DESIGNING A DEEP LEARNING INTEGRATED TEACHING MODULE IN AQIDAH AKHLAK SUBJECT IN MADRASAH ALIYAH - Era Auliyatul Faiza; Edi Nurhidin (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2026)
This article aims to explore the process of designing a deep learning-integrated teaching module for the Aqidah Akhlak subject. The research method used is descriptive qualitative at Ulil Albab Islamic Senior High School (MA), Kedawung Mojo, Kediri Regency. Data collection was conducted through interviews with Aqidah Akhlak teachers and documentation. This study found that teachers have systematically designed a deep learning-integrated teaching module with complete components in accordance with the Merdeka Curriculum framework. Three deep learning principles are integrated into two components of the teaching module: essential questions (containing mindful learning principles) and learning steps consisting of opening activities (containing joyful and mindful learning principles), core activities (containing joyful and meaningful learning aspects), and closing activities (containing mindful, meaningful, and joyful learning principles). Overall, integrating these three principles into the teaching module's components demonstrates that deep learning can be systematically applied to support holistic, student-centered learning planning. These findings suggest that developing a deep learning-integrated teaching module can serve as a reference for designing meaningful, contextualized instruction aligned with learning objectives. The contribution of this research lies in providing empirical evidence on the practice of integrating deep learning into teaching module components and in enriching the study of deep learning implementation in lesson planning within the context of the Merdeka Curriculum.